2004
DOI: 10.1590/s1676-06032004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e composição da ictiofauna de riachos da bacia do Rio Grande no estado de São Paulo, sudeste do Brasil

Abstract: Eighteen 100 m long streams stretches, none of an order higher than three, were sampled in three tributaries (six stream stretches sampled in each one) of the left margin of the main channel of Rio Grande (Rios Turvo, Pardo and Sapucaí) in the State of São Paulo, southeastern Brazil. Each stream stretch had its midpoint located with a GPS satellite receiver and had its fish fauna sampled via a standardized environmental data and fish collection methodology (primarily utilizing electrofishing) with the aim of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0
22

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 20 publications
9
61
0
22
Order By: Relevance
“…While Neotropical aquatic ecosystems tend to be dominated by siluriforms and characiforms (Castro, 1999), only the latter predominated in the present study. In general, the species identified in the present study were typical of those found in other hydrographic basins, such as those of the Rio São Francisco (Alves and Pompeu, 2010) and Rio Grande (Castro et al, 2004).…”
Section: Diversity Of Freshwater Bioindicatorssupporting
confidence: 74%
“…While Neotropical aquatic ecosystems tend to be dominated by siluriforms and characiforms (Castro, 1999), only the latter predominated in the present study. In general, the species identified in the present study were typical of those found in other hydrographic basins, such as those of the Rio São Francisco (Alves and Pompeu, 2010) and Rio Grande (Castro et al, 2004).…”
Section: Diversity Of Freshwater Bioindicatorssupporting
confidence: 74%
“…Esse número encontra-se dentro das estimativas de 6 a 15% de novas espécies para algumas porções do Alto Paraná, referidos recentemente por Castro et al (2003Castro et al ( , 2004Castro et al ( e 2005. Mantido o ritmo de descrições de novas espécies desta década, aproximadamente cinco por ano, levaríamos mais dez anos para descrever essas 50 espécies já reconhecidas, o que é um tempo demasiadamente longo.…”
Section: Táxons Novosunclassified
“…sificada, além de registrar a ocorrência de várias espécies alóctones e exóticas e mostrar que cerca de 6 a 15% das espécies referidas são novas (Castro et al 2003(Castro et al , 2004(Castro et al , 2005. Resultados semelhantes têm sido obtidos também por meio da revisão de coleções ictiológicas e de outros estudos independentes, reforçando o fato de que os levantamentos realizados no Alto Paraná são incompletos (Agostinho & Gomes 2005) e mostrando a importância de se incrementar esforços de coleta na área e de se revisar o material depositado em coleções.…”
unclassified
“…Identifying this species can be difficult due to its similarity to other species of the genus and the related genera Creagrutus, Piabina, and Bryconamericus. The species was first described from the Paraguay River basin (Eigenmann & Kennedy, 1903), and later reported from the Upper Paraná [6,[24][25][26][27] and São Francisco River basins [28]. Recently, our research group collected specimens of K. moenkhausii in the Paraíba do Sul River basin as well.…”
Section: Extraction Pcr and Sequencingmentioning
confidence: 99%